Imaginary Landscape No. 5: for any 42 phonograph records - Cage, John 1912-1992 (New York Peters, 1965)
This piece consist of only one movement and the average duration varies widely from recording to recording. It is scored for 42 recordings disposed in eight tracks in a mixing studio, all of them being re-recorded into tape as disposed in the score. The score itself is a block-grid, wherein each square is meant to be three inches of recording (around 0.2 seconds). The score also indicates the changes in dynamics and includes crescendos and diminuendos.[4] Whereas duration and amplitude are specified in the score, there is no mention from Cage as to what recordings or what type of music should be used for performing the piece. The compositional method was use of the I Ching, creating a chart work with a five to five structure, as in Imaginary Landscape No. 4 (March No. 2).
This piece was a part of Cage's two contributions to a project entitled Project for Music for Magnetic Tape, the other one being Williams Mix, composed in a similar fashion and also presented on graphic paper. However, the piece was to be realized as a tape recording, and not to be broadcast.With the help of long-time collaborator David Tudor and the technical assistance from Bebe and Louis Barron, Cage realized the composition on January 18, 1952. Cage used mostly jazz recordings to make this piece, which called for 42 recordings, presented as disposed in the score. This work became the basis of a dance piece, entitled Portrait of a Lady, which premiered in New York in 1952 by Jean Erdman.
Keywords: 20th Century (1901-2000); Aleatory music